Silent brain infarction and hypertension - Kobayashi, Shotai; Nagai, Atsushi; Suyama, Nobuo; Tsuchiya, Haruhisa; Yamaguchi, Suhei; Okada, Kazunori (Japanese Journal of Stroke, 1998)
We studied the relationship between silent brain infarction (SBI) and hypertension in stroke-free subjects who visited to brain check-up. The subjects with SBI showed significantly higher incidence of hypertension history, and higher blood pressure at brain check-up and at home than those without SBI. Duration of hypertension, daily blood pressure (BP), BP at brain check-up and condition of taking antihypertensive drugs did not relate to SBI in hypertensive subjects. In prospective study, higher incidence of stroke onset was observed in the subjects who showed higher BP at brain check-up and in hypertensives with SBI than those without. Hypertensives with family history of stroke showed significantly greater incidence of stroke onset than those without. These results indicate that not only hypertension but some genetic factors may contribute to stroke onset from SBI.